STUDIES ON LIBIDO AND SERUM TESTOSTERONE CONCENTRATION OF CHOLISTANI AI BULLS UNDER STRESS FREE AND STRESSFUL SEASONS - S. A. Mahmood; A. Ijaz; N. Ahmad; H. U. Rehman; H. Zaneb; U. Farooq Semen Production Unit; Karaniwala; Bahawalpur; Pakistan (Journal of Animal and Plant Sciences, 2013)
The study was executed with a specific objective to assess baseline data on libido indices (reaction time, libido index and time lapsed between two ejaculates) and serum testosterone concentration of Cholistani AI bulls (n=06) being reared at SPU, Karaniwala, Bahawalpur, Pakistan. Furthermore, influence was noticed on these parameters of stress free and stressful seasons. Four seasons of 2 months duration each were defined as i) stress free autumn (October-November), ii) stressful winter (December-January), stressful dry summer (May-June) and iv) stressful wet summer (July-August).   The overall mean (±SEM) values for Reaction Time, libido index and Time Lapsed between Two Ejaculates in the present study were 4.5±1.10 min, 3.48±0.03 and 3.04±0.30 min, respectively. Non-significant (P>0.05) differences were found in all the parameters during four seasons. The overall mean value for serum testosterone concentration was 5.81±0.32ng/mL with no influence of seasons on it. In a nutshell, the Cholistani AI bulls maintain their serum testosterone concentration at a constant level during stress free and stressful seasons, hence keeping their libido indices constant, too. This is indicative of the fact that this breed has an innate ability of being well adapted to the harsh, hot desert climate. This adaptability, in turn, helps them maintain their reproductive abilities at optimum levels even in stressful seasons. This preliminary study envisages for a broader study both on fresh and post thaw seminal indices adjunct with fertility trial in this neglected indigenous cattle breed of Pakistan.
Keywords: Cholistan; stress; libido; reproductive indices